Being modern in Lahore: Islam, class and consumption in urban Pakistan - Maqsood, A (2012)
This thesis, based on 14 months of fieldwork, examines middle-class Lahore, a milieu that is not only anxious about the growing religious violence in the country but also feels disappointed by the state and its false promises of progress. The ethnography explores how such tensions shape ideas on personal and public piety which, in turn, influence conceptions of modernity and a ‘successful life’. I examine the growing presence of a form of religiosity that emphasises the personal study of the Quran and other Islamic texts. The rising popularity of Quran schools and study circles, talks by television-based Islamic scholars, and discussions in homes are indicative of a sensibility which encourages individuals to discover the ‘real’ and ‘rational’ Islam by understanding the Quran for themselves. Although this religiosity centres around the individual and the cultivation of personal ethics, it also has a significant public aspect. Many believe that acquired Islamic ethics will not only help attain success in this life and the hereafter but also solve societal problems such as corruption, nepotism and economic disorder. Although such ideas have developed alongside a belief that the state is incompetent, they nevertheless reproduce many state-produced discourses on religion, morality and modernity. At a broader level, my thesis is concerned with how middle-class Pakistan perceives itself and its position in the world. I argue that prevailing ideas on Islam have been shaped by increased communication with the South Asian diaspora abroad and have developed in response to two struggles. First, the emerging middle-class uses this religiosity to contest the moral and economic domination of the established old-money elite. Second, anxieties about the gaze of an abstracted outsider – usually the West on the Muslim world – shape middle-class representations of self.